Maternal androgen excess significantly impairs sexual behavior in male and female mouse offspring: Perspective for a biological origin of sexual dysfunction in PCOS - Donaldson, Nina M.; Prescott, Melanie; Ruddenklau, Amy; Campbell, Rebecca E.; Desroziers, Elodie (Frontiers in Endocrinology, 2023)
Polycystic ovary syndrome (PCOS) is the most common infertility disorder worldwide, typically characterised by high circulating androgen levels, oligo- or anovulation, and polycystic ovarian morphology. Sexual dysfunction, including decreased sexual desire and increased sexual dissatisfaction, is also reported by women with PCOS. The origins of these sexual difficulties remain largely unidentified. To investigate potential biological origins of sexual dysfunction in PCOS patients, we asked whether the well-characterized, prenatally androgenized (PNA) mouse model of PCOS exhibits modified sex behaviours and whether central brain circuits associated with female sex behaviour are differentially regulated. As a male equivalent of PCOS is reported in the brothers of women with PCOS, we also investigated the impact of maternal androgen excess on the sex behaviour of male siblings. Adult male and female offspring of dams exposed to dihydrotestosterone (PNAM/PNAF) or an oil vehicle (VEH) from gestational days 16 to 18 were tested for a suite of sex-specific behaviours. PNAM showed a reduction in their mounting capabilities, however, most of PNAM where able to reach ejaculation by the end of the test similar to the VEH control males. In contrast, PNAF exhibited a significant impairment in the female-typical sexual behaviour, lordosis. Interestingly, while neuronal activation was largely similar between PNAF and VEH females, impaired lordosis behaviour in PNAF was unexpectedly associated with decreased neuronal activation in the dorsomedial hypothalamic nucleus (DMH). Taken together, these data link prenatal androgen exposure that drives a PCOS-like phenotype with altered sexual behaviours in both sexes.